Enhancing the electrochemical performance of high-voltage materials in Li-ion cells using additive-based electrolytes - Ungureanu, Cosmin; Melinte, Adina; SpÎnu-Zăuleț, Adnana; Rizoiu, Alexandru; Fantini, Sébastien; Elkjæ r, Christian Fink; Buga, Mihaela; Necula, Horia (Scientific Bulletin. Series C, Electrical Engineering and Computer Science, 2025)
Lithium-ion batteries (LIB) are essential for energy storage, providing high energy density, long cycle life, and low self-discharge rates. Increasing market demand requires improvements in LIB performance, particularly in cycling stability. This study investigates carbonate-based electrolytes with additives to mitigate capacity fading due to LiPF6 decomposition. The high-voltage spinel material LNMO was evaluated in half-cell configurations against metallic lithium, utilizing carbonatebased electrolytes with different additives. The Lithium Nickel Manganese Oxide (LNMO) cathode demonstrated a specific capacity of 116 mAh/g at 3C and exceeding 115 mAh g-1 at 1C, with over 85% capacity retention after 120 cycles, highlighting its potential to enhance LIB technology.